Improving Students' Digital Literacy through Technology: The Importance of Information Seeking Skills - Husna Syafrida Putri; Anggita Joito Grace; Nia Ramadani Siregar; Joharis Joharis (International Journal of Educational Evaluation and Policy Analysis, 2025)
The development of digital technology has transformed how university students access and process information. Digital literacy has become an essential skill encompassing the ability to search for, evaluate, and effectively use information. This study aims to analyze the factors influencing university students' digital literacy, the role of technology in supporting these skills, and effective strategies that can be implemented to improve digital literacy in academic environments. The research method employed is a mixed-method approach with data collection techniques through digital questionnaires administered to 25 students from various majors, as well as a literature review from various sources. The results of the study show that 52% of students use the internet for more than six hours a day, 83.3% actively seek information daily, and 60% always verify information before sharing it. The main obstacles in improving digital literacy include limited access to digital learning resources (54.2%) and a lack of literacy training (54.2%). Proposed strategies to address these challenges include integrating digital literacy materials into the curriculum, organizing regular training and seminars, and optimizing the use of educational technology platforms. The conclusion of this study emphasizes that digital literacy is not just about technical skills but also involves critical thinking and filtering accurate information. Therefore, systematic efforts are needed from various parties, including universities, lecturers, and students, to create an academic environment that supports the optimal development of digital literacy.